If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = (x + 1)(x + 2) + 8 Reorder the terms: 3x = (1 + x)(x + 2) + 8 Reorder the terms: 3x = (1 + x)(2 + x) + 8 Multiply (1 + x) * (2 + x) 3x = (1(2 + x) + x(2 + x)) + 8 3x = ((2 * 1 + x * 1) + x(2 + x)) + 8 3x = ((2 + 1x) + x(2 + x)) + 8 3x = (2 + 1x + (2 * x + x * x)) + 8 3x = (2 + 1x + (2x + x2)) + 8 Combine like terms: 1x + 2x = 3x 3x = (2 + 3x + x2) + 8 Reorder the terms: 3x = 2 + 8 + 3x + x2 Combine like terms: 2 + 8 = 10 3x = 10 + 3x + x2 Add '-3x' to each side of the equation. 3x + -3x = 10 + 3x + -3x + x2 Combine like terms: 3x + -3x = 0 0 = 10 + 3x + -3x + x2 Combine like terms: 3x + -3x = 0 0 = 10 + 0 + x2 0 = 10 + x2 Solving 0 = 10 + x2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x2' to each side of the equation. 0 + -1x2 = 10 + x2 + -1x2 Remove the zero: -1x2 = 10 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -1x2 = 10 + 0 -1x2 = 10 Divide each side by '-1'. x2 = -10 Simplifying x2 = -10 Reorder the terms: 10 + x2 = -10 + 10 Combine like terms: -10 + 10 = 0 10 + x2 = 0 The solution to this equation could not be determined.
| 4(6+2x)=0 | | x+15=2(x-10) | | x+15=2(x-15) | | 8w-11=-8w | | 3x=11+1 | | -7x-10=-3x-14 | | 2x+2y=22 | | 8w+40=0 | | 3x+1y=20 | | 11.6b+2=3.8b+38.66 | | 11.4x+3=5.7x+28.08 | | 3x-2=-x+2 | | 13x+4=5x+12 | | 5y=-25x+30 | | -12=3(2x-8) | | 5q-2(1-q)=3q | | 12=4y | | 4x-7=-19 | | -4x-2=-x-5 | | 5x+20=3x+4 | | 15=-8(b-1)+9 | | 4c+3=-21 | | 3s=66 | | 8v=32 | | -6+2n+6=0 | | 15=4z+11 | | 105=21t | | 2(t-7)-3(2t-3)=10-6(3t+5) | | -3x-2=-x+4 | | 6X-12=X+4 | | 10w=150 | | 2(6z-1)-5(z+8)=3(z+1) |